A MEMS platform for the dielectrophoretic and thermoelectric characterization of Bi2Te3 nanowires - Wang, Z.; Toellner, W.; Adhikari, S. S.; Kroener, M.; Kojda, D.; Mitdank, R.; Fischer, S. F.; Nielsch, Kornelius; Woias, P. (2013 Transducers and Eurosensors XXVII: The 17th International Conference on Solid-State Sensors, Actuators and Microsystems, TRANSDUCERS and EUROSENSORS 2013, 2013)
We demonstrate the fabrication and use of our second generation Thermoelectric Nanowire Characterization Platforms (TNCP). The design of this TNCP results from an extensive experimental study on dielectrophoretic (DEP) nanowire manipulation and placement on a DEP test structures. These TNCPs fabricated with optimally designed DEP electrodes have enhanced the nanowire assembly yield up to 90%. As a practical application, measurements of electrical conductivity (σ) and Seebeck coefficient (S) of an individual Bi 2Te3 NW are reported. Finally, another novel method for NW assembly is introduced, using an optical tweezers. © 2013 IEEE.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Bi; DEP test structure; dielectrophoresis; nanowire assembly; optical tweezers; TNCP